Strategic Management to Envisage the Challenges of Inclusive Economy and Business Innovation: A Bibliometric Study - Adiatma, Tini; Irianto, Okto; Siamsa, Simon; Suwandi, Yudi W. (Journal of International Conference Proceedings, 2023)
Strategic management can be used to envisage the challenges of inclusive economy and business innovation. This study aims to analyze the research trends development on strategic management. This research uses bibliometric analysis visualization using VosViewer. The database was downloaded from ScienceDirect. The advanced search limitation using the keyword “strategic management” in 2022. The research filter to research articles, focusing only on business, management, and accounting. The results show there are 784 articles. Analysis of visual bibliometrics shows the trend of the themes and the author's relation. There are three clusters on publication article analysis. The strongest topics in cluster 1 related to strategic management publication are firm, data, effect, role, relationship, model, and impact all of each item strengths above 1000; in cluster 2 about process, development, and framework which all around 900; and all in the third cluster no more than 500 link strength. The most productive author of this research in 2022 is Vijay Pereira.